2012
DOI: 10.1038/mi.2012.72
|View full text |Cite
|
Sign up to set email alerts
|

A role for mucosal IL-22 production and Th22 cells in HIV-associated mucosal immunopathogenesis

Abstract: Interleukin-22 (IL-22) is a cytokine with epithelial reparative and regenerative properties that is produced by Th22 cells and by other immune cell subsets. Therefore, we explored the hypothesis that disruption of the gut barrier during HIV infection involves dysregulation of these cells in the gastrointestinal mucosa. Sigmoid IL-22-producing T cell and Th22 cells were dramatically depleted during chronic HIV infection, epithelial integrity was compromised, and microbial translocation was increased. These alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
158
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(170 citation statements)
references
References 38 publications
9
158
2
1
Order By: Relevance
“…IL-22 is important for the maintenance of the intestinal mucosa integrity. It has been previously shown that chronic HIV infection leads to the exhaustion of Th22 cell subset [30]. However, our study showed increased concentrations of IL-22 in chronic HIV-1 infection and this issue requires further investigations.…”
Section: Discussioncontrasting
confidence: 50%
“…IL-22 is important for the maintenance of the intestinal mucosa integrity. It has been previously shown that chronic HIV infection leads to the exhaustion of Th22 cell subset [30]. However, our study showed increased concentrations of IL-22 in chronic HIV-1 infection and this issue requires further investigations.…”
Section: Discussioncontrasting
confidence: 50%
“…However, increased systemic microbial translocation (i.e., plasma LPS levels) was only apparent during chronic HIV infection, whereas a dramatic impairment of Th17 function was apparent very early after HIV acquisition. We hypothesize that this delayed impact of Th17 functional impairment on mi- crobial translocation may be because a loss of epithelial integrity is also needed for microbial translocation to occur, and this integrity is only compromised later in HIV infection, coincident with the loss of mucosal IL-22 production capacity (2,4). Although the polyfunctional capacity of mucosal Th17 cells was reduced during untreated HIV infection, this was not directly associated with microbial translocation or systemic immune activation.…”
Section: Discussionmentioning
confidence: 95%
“…Th17 cells were defined as IL-17a + CD4 T cells, and Tregs were defined as FOXP3 and CD25 dually positive CD4 T cells. The absolute number of gut cells was determined by multiplying the percentage of live lymphocytes, determined by flow cytometry, by the number of gut cells/g of tissue, as previously described (2,34). Th17 cell polyfunctionality analysis was generated by Boolean gating analysis using FlowJo software, and a minimum event number of 50 was set for Th17 polyfunctionality analyses.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Th17 and Th22 populations are involved in the generation of immune responses to microbial pathogens at mucosal surfaces and play a critical role in normal barrier homeostasis [18,62] (reviewed by [63]. In HIV infection, Th17 and Th22 cells are depleted more severely than the bulk CD4 + T cell population in the intestinal compartment [64,65]. The strong depletion of these cells is associated with the development of malabsorption and nutriment complications in rhesus macaques [66] and with a decreased expression of markers regulating barrier integrity and intestinal function [67,68].…”
Section: The Gastro-intestinal Lymphoid Tissue (Galt)mentioning
confidence: 99%